Pollen morphology of certain species of the family Lamiaceae in Saudi Arabia - Abdullah R. Doaigey (Saudi Journal of Biological Sciences, 2018)
The intention of the present wok is to provide an account on the pollen morphological features of Lamiaceae in Saudi Arabia as a basis for future studies of Lamiaceae pollens in the region. Pollen morphology of 20 species belong to 16 genera of the Lamiaceae has been investigated using Light Microscope (LM) and Scanning Electron Microscope (SEM). The study revealed that the pollen grains were characterized by 3-zonocolpate or 6-zonocolpate. Size of the pollen is variable between the genera but not among the species of the same genus. The surface pattern of the exine varies from fine reticulate, rough reticulate, mega-reticulate, reticulate-perforate, bireticulate-perforate or granulate, leading to 6 types of pollen grains. These variations revealed by this study implies that pollen Morphology may be of significant value sharing in solving problems in the classification of Lamiaceae members. A Key to the species, based on the morphological features of pollen grains, is also provided.